New Venture Creation - Success Factors and The Business Life Cycle - Farzad, Photographer (2010)
This paper aims to throw light on the process of new venture creation and the factors affecting the success of small and new businesses. I will also cover the business life cycle with relation to our entrepreneurial venture, In-Sight. Theories highlighting the ingredients of a successful start-up in relation to my experience while planning the set-up of “In-Sight Inc” are what I wish to discuss in the chapters to follow. This exercise i believe, has give me an insight into what I would require to become a successful entrepreneur and successfully launch a venture on my own. It has helped me understand the stages through which a business goes in its lifetime and what are the best practices to follow at each stage.